Validity and reliability of a behavior-based food coding system for measuring fruit, 100% fruit juice, vegetable, and sweetened beverage consumption: results from the Girls Health Enrichment Multisite Studies - Cullen, Karen W; Himes, John H; Baranowski, Tom; Pettit, Janet; Stevens, Mary; Slawson, Deborah Leachman; Obarzanek, Eva; Murtaugh, Maureen; Matheson, Donna; Sun, Wanjie; Rochon, James (Preventive medicine, 2004)
Background. This paper presents the rationale, reliability, and validity of a behavior-based food coding system for measuring fruit (F), juice (J), vegetable (V), sweetened beverage, and water consumption in children. Methods. Coding algorithms for FJV, sweetened beverages, and water were developed for use with the Nutrition Data System for Research (NDS-R). Two hundred and ten 8- to 10-year-old African American girls at four field centers completed two 24-h dietary recalls at baseline and at 12 weeks follow-up after a weight gain prevention intervention. Differences in mean baseline consumption of selected food variables and other selected nutrients across the four field centers were analyzed. Intraclass correlation coefficients (ICCs) for reliability across 2 days of food recalls and 12-week test–retest reliability correlations were calculated. For the purposes of this paper, nutrient intake estimates were considered construct validators of food intake, and validity was assessed by correlating the coded food variable servings with nutrient intake. Results. ICCs varied from zero (0.001 for beta carotene equivalents) to moderate (0.44 for sucrose), indicating substantial instability in consumption or reporting. Twelve-week test–retest correlations were slight to moderate (0.09 for lycopene to 0.49 for folate). FJV consumption was negatively related to percent energy from fat ( r = −0.28; P = 0.001) and positively related to other nutrients. Sweetened beverage consumption was positively related to energy, sucrose, fructose, and vitamin C consumption. Conclusions. This behavior-based food coding system demonstrated construct validity among 8- to 10-year-old African American girls and can measure the desired food groups.